Implementasi Model Teams Games Tournament (TGT) Menggunakan Media Gurita Penjumlahan Pembelajaran Matematika SD 1 Terong Tawah - Mutiara Alisa; Herlin Juniarti; Ainul; Dende Fitriya Wirayani; Muhammad Erfan (Primera Educatia Mandalika: Elementary Education Journal, 2025)
This study aims to describe the implementation of the Teams Games Tournament (TGT) learning model using the Octopus Addition media in Mathematics learning at SDN 1 Terong Tawah. The study used a descriptive qualitative approach. The subjects were 28 third-grade students. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the implementation of the TGT model using the Octopus Addition media worked well, following the learning syntax, which included class presentations, teamwork, games, tournaments, and group awards. Students demonstrated high levels of activity and enthusiasm throughout the learning process, both during group discussions and during academic games and tournaments. The use of the Octopus Addition media helped students understand the concept of addition more concretely and visually. Thus, the TGT learning model using the Octopus Addition media can be an effective alternative Mathematics learning strategy to increase elementary school students’ engagement, motivation, and understanding of addition.